If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 + x + x + 3 * 2 = 34 Multiply 3 * 2 x + 3 + x + x + 6 = 34 Reorder the terms: 3 + 6 + x + x + x = 34 Combine like terms: 3 + 6 = 9 9 + x + x + x = 34 Combine like terms: x + x = 2x 9 + 2x + x = 34 Combine like terms: 2x + x = 3x 9 + 3x = 34 Solving 9 + 3x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 34 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 34 + -9 3x = 34 + -9 Combine like terms: 34 + -9 = 25 3x = 25 Divide each side by '3'. x = 8.333333333 Simplifying x = 8.333333333
| 9x+2y+7z-5x+3z-4y= | | x^2+xy+xy^2=0 | | x^2(1-x)=1 | | (4-5i)-(9+4i)= | | (X+3)*2=81 | | 60x+9x^2=100 | | (X+3)*2=0 | | x^2-x=2450 | | sqr(25)=x | | X(60+9x)=100 | | (x-3)x(x+1)=0 | | 31-6c=13 | | 2x-6=12x-20 | | 4x*2-1=0 | | Iz+1=i | | 4y*4= | | 1-3(2x+5)=4(x-3)-3(x-2) | | (5x+4)-10=24 | | z^2+4iz+8=0 | | x^2-14x=241 | | 20y-15y^2= | | xz+yt+xt+yz= | | 2x+7=5x-9 | | x^2-4x+11=-6x-3 | | 3(1+11x)= | | 4a^2-12a= | | 2.8x+15=12-1.2x | | y=(x-2) | | 2-3r=-4 | | 4j-5=3 | | -12(x-1)=2(-2x) | | 7(2x+3)=3(3x-2) |